How Hierarchal Positions Affect Employees’ Knowledge Sharing Behaviors? An Exploratory Study (Journal of Organizational Psychology, 2017)
This paper explores the differences in employees’ knowledge sharing behaviors when interacting with targets from different hierarchal positions in an organization. Eleven mid-level employees working in small and medium-sized enterprises in Hong Kong were interviewed for the exploratory purpose. The interview corpus, which consisted of 30,000 words, showed how and why mid-level employees differ in their knowledge sharing with different target audiences: their superiors, peers and subordinates. Theoretically, the findings advance our understanding of employees’ decisions on knowledge sharing behavior; and, in practical terms, the findings inform managers about how employees’ behavior is affected by hierarchal relationships in the workplace.
Keywords: Organizational Psychology; Hierarchal Positions; knowledge sharing behaviors